An approach to enhance the durability and mechanical properties of Class G cement using nano materials - Tiong, M. (Institute of Physics Publishing, 2019)
Maintaining the integrity of the cement used to seal off the injection intervals of sequestrations sites is crucial to confine CO2 for thousands of years. There have been many studies to resolve the issue of cement degradation induced in the presence of CO2, but a very limited success has been reported to the application of the approaches proposed so far. Nano materials have gained the attention of many researchers in the past decade and might be able to resolve the issue of cement degradation given their outstanding performance and proven applications in the civil and polymer industries. In this paper, attempts are made to improve the physical and mechanical characteristics of class G cement using nano glass flakes (NGFs) and multiple-walled carbon nanotubes (MWCNTs). To do this, different cement-nanocomposites were prepared using two mixing techniques and their physical and mechanical changes were evaluated under different curing conditions. Samples with cylindrical shape of were prepared and cured under the temperature of 50Â°C and atmospheric pressure for 1 days. The results obtained indicated both nanoparticles are neutrally stable and may have a very slight effect on the cement rheology but may significantly increase the strength of the cement. It was concluded that the cement with 0.05 wt. MWCNTs can provide the best results in terms of rheology, compositional changes and compressive strength. Â© Published under licence by IOP Publishing Ltd.